1999
DOI: 10.1053/bbmt.1999.v5.pm10465102
|View full text |Cite
|
Sign up to set email alerts
|

Graft-facilitating doses of ex vivo activated gammadelta T cells do not cause lethal murine graft-vs.-host disease

Abstract: The purpose of this study was to examine the ability of gamma(delta) T cells to cause graft-vs.-host disease (GVHD) after allogeneic bone marrow transplantation (BMT) and to determine whether these cells offered any therapeutic advantages relative to alphabeta T cells. Due to the paucity of naive gamma(delta) T cells in mice and humans, gamma(delta), T cells (obtained from alpha(beta) T cell-deficient murine donors) were ex vivo activated and expanded in interleukin (IL)-2 so as to achieve sufficient cell numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
42
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(45 citation statements)
references
References 28 publications
3
42
0
Order By: Relevance
“…Data from our laboratory and others indicate that gd T cells do not require MHC class II for their maturation 37 or proliferation in response to an allogeneic MHC disparity 38 and are not initiators of GvHD. 39 Moreover, Drobyski 40 showed that large doses of interleukin-2 (IL-2) expanded gd 41 showed that although activated gd and naive ab T cells exacerbated GvHD when infused together, delaying the infusion of ab T cells by 2 weeks resulted in improved survival. These findings are consistent with Ellison,42 who noted that gd T cells could be activated in the GvHD reaction but found no evidence that GvHD was initiated by gd T cells.…”
Section: Discussionmentioning
confidence: 99%
“…Data from our laboratory and others indicate that gd T cells do not require MHC class II for their maturation 37 or proliferation in response to an allogeneic MHC disparity 38 and are not initiators of GvHD. 39 Moreover, Drobyski 40 showed that large doses of interleukin-2 (IL-2) expanded gd 41 showed that although activated gd and naive ab T cells exacerbated GvHD when infused together, delaying the infusion of ab T cells by 2 weeks resulted in improved survival. These findings are consistent with Ellison,42 who noted that gd T cells could be activated in the GvHD reaction but found no evidence that GvHD was initiated by gd T cells.…”
Section: Discussionmentioning
confidence: 99%
“…Along these lines, in a murine model of MHC-incompatible allogeneic bone marrow transplantation, injection of ex vivo activated and expanded ␥␦ T cells has been demonstrated to facilitate engraftment. 10 A role of NK cells in transplantation was initially described in 'hybrid resistance', in which F1 hybrid recipients reject parental bone marrow grafts, while accepting solid tissues. 11,12 More recently, in a murine model of MHC-incompatible allogeneic bone marrow transplantation, Murphy et al showed that infusion of in vitro IL-2 activated NK cells could prevent the development of graft-versus-host disease (GVHD), exert an anti-tumoral effect against a co-transplanted tumor cell line, and increase survival in recipient mice.…”
Section: Introductionmentioning
confidence: 99%
“…Several in vitro and in vivo studies have shown that gd T cells and NK cells induce potent antitumor effects without causing GVHD. [28][29][30][31] In addition, these innate lymphocytes may facilitate engraftment of human stem cells [32][33][34] and are even able to prevent or mitigate GVHD. 35 These findings are consistent with a recent analysis by Godder et al, 36 who demonstrated a long-term survival advantage without increased GVHD incidence in a group of high-risk acute leukemia patients recovering with increased gd T cells after partially mismatched related donor marrow transplantation.…”
Section: Discussionmentioning
confidence: 99%